Can Psychiatry Be Both a Medical Science and a Healing Art? The Case for Polythetic Pluralism. - Pies, Ronald W. (Psychiatric Times, 2011)
The author contends that psychiatry ought to be both a medical science and a healing art. He says that psychiatry should be a medical science in so far as it studies conditions of disease and health. He adds that psychiatry should be a healing art in so far as it concerns itself with the inner world and intimate subjectivity of the patient. He also mentions the absence of conflict or incompatibility between these complementary realms.